SHORT-TERM OUTCOMES OF LAPAROSCOPIC COLORECTAL RESECTIONS FOR CANCER: A FIVE-YEAR SINGLE-CENTRE EXPERIENCE FROM SERBIA - Milev, Boško; Dragović, Saša; Bezmarević, Mihailo; Jocić, Miodrag; Stevanović, Jovana; Pantić, Ivan; Mitrović, Miroslav; Petković, Srđan; Mirković, Darko; Ćorović, Irfan; Plojović, Haris; Filip; et al. (Medicinski časopis, 2025)
Objective: To evaluate the short-term outcomes of laparoscopic colorectal resections for colorectal cancer in a single Serbian tertiary centre. Methods: A retrospective cohort study included 97 patients who underwent elective laparoscopic colorectal resections between January 2018 and March 2023. Demographic, perioperative, and oncologic data were analyzed. Primary outcomes were 30-day morbidity and mortality; secondary outcomes included operative time, conversion, re-intervention, length of stay, and lymph-node yield. Logistic regression identified independent predictors of complications. Results: The cohort comprised 59 men (60.8%) and 38 women (39.2%), with a median age of 71 years. Conversion to open surgery occurred in 6 patients (6.1%), while re-intervention was required in 3 (3.1%). The median operative time was 120 minutes for colonic and 175 minutes for rectal resections. Median lymph-node yield was 15, with all achieving R0 resection. The overall 30-day morbidity rate was 17.5%, with no perioperative deaths. General complications occurred in 12.4% and surgery-specific complications in 11.3%, with partial overlap. Median length of stay was 9 days, significantly longer in men and diabetic patients. Logistic regression confirmed cardiomyopathy as an independent predictor of postoperative complications (OR 7.5, p = 0.008). Conclusion: Laparoscopic colorectal resections in this series were associated with acceptable morbidity, no mortality, low conversion, and adequate oncologic quality. Cardiomyopathy was identified as a major perioperative risk factor, highlighting the need for tailored perioperative management.